Causal Connections, Logical Connections, and Skeptical Theism: There Is No Logical Problem of Evil - Hendricks, Perry (Religions, 2022)
In this paper, I consider Sterba’s recent criticism of skeptical theism in context of his argument from evil. I show that Sterba’s criticism of skeptical theism shares an undesirable trait with all past criticisms of skeptical theism: it fails. This is largely due to his focus on causal connections and his neglect of logical connections. Because of this, his argument remains vulnerable to skeptical theism.